Feeding behavior in three-year-old children born <30 weeks and term-born peers. (1st November 2018) - Sanchez, Katherine; Boyce, Jessica O.; Morgan, Angela T.; Spittle, Alicia J.
Abstract: Background: Feeding difficulties threaten growth, health and neurodevelopment, and are prevalent among infants born preterm. The literature differs on (i) whether these problems persist into early childhood, and (ii) risk factors in the preterm population. In this study we explore feeding difficulties and risk factors in preterm and term-born three-year-olds. Objectives: To determine whether three-year-olds born <30 weeks have poorer feeding outcomes than their term-born peers; and identify predictors of feeding outcomes in children born <30 weeks. Methods: Feeding outcomes were examined in three-year-old children born <30 weeks, and a term-born comparison group, using parent report and the Behavioral Pediatric Feeding Assessment Scale (BPFAS). Factors hypothesized to be associated with feeding difficulties and preterm birth were examined in the preterm group, including: gestational age at birth, birth weight z-score, chronic lung disease (CLD), nasogastric tube (NGT) feeding at hospital discharge, age at breastfeeding cessation, oromotor feeding impairment at 12 months, weight at 12 months in kilograms and neurodevelopmental diagnoses. Results: In 217 children (111 born <30 weeks, 106 term-born), parents of children born <30 weeks reported more feeding concerns on parent report questions than parents of term-born peers. CLD, NGT at discharge, neurodevelopmental diagnoses and weight at 12 months predicted these parent-reported outcomes. By contrast, there was no difference in BPFAS results between preterm and term groups, and BPFAS scores were predicted only by birth-weight z-score in the preterm group. Conclusions: Behavioral feeding outcomes for three-year-old children born <30 weeks were equivalent to term-born peers in this study, however parental concerns about feeding differed. Further investigation is required to identify the drivers of parent concerns about feeding. Children displaying core risk factors warrant specific follow-up of feeding outcomes.